Video-analisi e videografia - Knoblauch, Hubert; Tuma, René; Schnettler, Bernt (SocietàMutamentoPolitica, 2016)
In this article, we discuss the use of video data for qualitative social research and its particular practicality for studying face-to-face interaction. The special focus is on naturally occurring data and its analysis. Whereas ‘video analysis’ refers to the process of analysing audio-visual data, videography means the encompassing process of collection video data in the field, its interpretation and its analysis.